The Government budget and development - Gunatilleke, Godfrey; Gunatilleke, Godfrey; Shanmugam Chandi; Shanmugalingam K; Wijeyeratne Eymard de Silva; Marga Institute (Colombo, Sri Lanka : Marga Institute, 1994)
With reference to Sri Lanka.
"Copyright reserved, Marga Institute"--T.p. verso.
Keywords: Budget -- Sri Lanka; Sri Lanka -- Economic policy